Features of construction systems of distributed content-monitoring of global information networks - Lande, Dmytro; Kondratenko, Yaroslav (Collection "Information Technology and Security", 2017)
The properties of information flows are examined taking into account their belonging to segments of global networks. The article describes how to implement content-monitoring with taking to account continuous increasing complexity of the Internet segments and available for use practical methods of construction of distributed content monitoring systems. Particular importance attaches to this issue in carrying out activities aimed at preventing, timely detection, termination or neutralization of real and potential threats to state information security. Organization of effective counteraction to the challenges and threats to national security and its specific manifestations in the information sphere is one of the urgent tasks, the solution of which is an important task in terms of building civil society and the rule of law. Capture and synthesis of large dynamic content streams that are continuously generated in the Internet space requires qualitatively new methods and approaches to implement information security measures. Study of information needs and requirements formation for the implementation of similar systems suggests that the usage of distributed (segmented) content monitoring of global networks/media and f full set of interaction interfaces of segments of global networks and their monitoring tools is important in the process of content monitoring (scanning) of the Internet. The complexity of segments of the Internet as a software and technical objects is essential, not a secondary property. Designing software and hardware for distributed content monitoring of global networks / media, abstracting from both their complexity and their essence. The solution of such problems is based on the InfoStream content monitoring system. When building expert systems of distributed content monitoring, perceived the need to consider the level of popularity (availability) segment of the Internet and its efficiency in shaping the content, of different approaches to collecting and providing information interfaces interaction, so each “singled-out” segment of the global Internet is expedient of forming own knowledge base and receptions.